Addressing Changes In Work Practices Due To Covid-19 In Banking Sector (Journal of Namibian Studies : History Politics Culture, 2023)
issues, a lack of digital maturity, and stress on the current infrastructure are making the problem worse as businesses hurry to address COVID-19's effects on financial services. Banks undoubtedly have a lot on their plates in light of the recent COVID-19 new coronavirus epidemic. The population and sample of this study, which used quantitative methodologies, were workers of Canara banks. SPSS 20 was used to process the incoming data. The findings demonstrated that compensation and job motivation had an impact on employee performance at the same time, with compensation having the greatest impact on banking workers' performance during the Covid-19 epidemic.